(untitled) (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2021)
This paper focuses on the iconography of gryphomachia on Apulian pottery. The motif of the battle between Arimaspians and griffins for Apollo’s gold, which is also known by literary sources, is widespread in Attic production, starting from the IV century B.C. On the basis of published works, the griffin’s image turns out to be the main decoration on the small vessels or the secondary iconographic repertoire on necks and feet of large volute kraters, while only eleven vases show the scene of the struggle. As this paper tries to show, the uses of griphomachia theme can be referred to a funerary context.